Language Utterance Among India Community In Padang - Fajrina Putri Farisya (Jurnal Ilmiah Langue and Parole, 2017)
This thesis title is Language Utterance Among India Community in Padang The writer focusing on the language that utter among India community in Padang. The India people usual talk and communication with other with mix language which another did not know. The writer seek this as uniqueness that can be describe by code mixing theory and sociolinguistik. The writer uses sociological theory for reach the purposes of the research. Purposes of the research is to descirbe the language change that happen in India community in Padang.. language change that happens have relate with linguistic theories. After getting the data, the writer , makes formula from the code mixing that utter in India community in Padang. This research uses field research method for get the significant data and library research for get the theories that will be uses as basic theory in this thesis. Technique collecting of data is qualitative method, which the writer get the data from 7 qualified interviewee based on criteria ( NORM (Nonmobile Older Rural Males). From it, the writer uses record technique for get the data. The results from the research that has been done, the wrier finds language change that influence by another ethnic such Minang, Tionghoa Padang and Indonesia. The changing are, vowel /i/ change into /e/ in medial, disappearance /h/ in final,initial and medial. Disappearance /r/ in final and medial, absorption /at/ become /?/ in final,absorption /u/ become /o/ in medial and final, absorption /t/ become /k/ in final, absorption /a/ into /o/ in final, absorption /p/ into /?/, absorption/ŋ/ into /aŋ/ in final, absorption /e/ become /a/ in medial and initial. Disappearance /e/ in medial, disappearance /d/ in initial, and medial,also disappearance /p/ in final. Code mixing that utter by India community that has been describe by code mixing theory, and become a formula from it.